Different Infection Profiles and Antimicrobial Resistance Patterns Between Burn ICU and Common Wards - Gong, Yali; Peng, Yuan; Luo, Xiaoqiang; Zhang, Cheng; Shi, Yunlong; Zhang, Yixin; Deng, Jun; Peng, Yizhi; Luo, Gaoxing; Li, Haisheng (Frontiers in Cellular and Infection Microbiology, 2021)
Infection is the leading cause of complications and deaths after burns. However, the difference in infection patterns between the burn intensive care unit (BICU) and burn common wards (BCW) have not been clearly investigated. The present study aimed to compare the infection profile, antimicrobial resistance, and their changing patterns in burn patients in BICU and BCW. Clinical samples were analyzed between January 1, 2011, and December 31, 2019, in the Institute of Burn Research in Southwest China. The patient information, pathogen distribution, sources, and antimicrobial resistance were retrospectively collected. A total of 3457 and 4219 strains were detected in BICU and BCW, respectively. Wound secretions accounted for 86.6% and 44.9% in BCW and BICU, respectively. Compared with samples in BCW, samples in BICU had more fungi (11.8% vs. 8.1%), more Gram-negative bacteria (60.0% vs. 50.8%), and less Gram-positive bacteria (28.2% vs. 41.1%). Acinetobacter baumannii were the most common pathogen in BICU, compared with Staphylococcus aureus in BCW. S. aureus was the most frequent pathogen in wound secretions and tissues from both BICU and BCW. However, A. baumannii were the first in blood, sputum, and catheter samples from BICU. Overall, the multidrug-resistance (MDR) rate was higher in BICU than in BCW. However, the gap between BICU and BCW gradually shortened from 2011 to 2019. The prevalence of MDR A. baumannii and Klebsiella pneumonia significantly increased, especially in BCW. Furthermore, Carbapenem resistance among K. pneumoniae significantly increased in BICU (4.5% in 2011 vs. 40% in 2019) and BCW (0 in 2011 vs. 40% in 2019). However, the percentage of MDR P. aeruginosa sharply dropped from 85.7% to 24.5% in BICU. The incidence of MRSA was significantly higher in BICU than in BCW (94.2% vs. 71.0%) and stayed at a high level in BICU (89.5% to 96.3%). C. tropicalis and C. albicans were the two most frequent fungi. No resistance to Amphotericin B was detected. Our study shows that the infection profile is different between BICU and BCW, and multidrug resistance is more serious in BICU than BCW. Therefore, different infection-control strategies should be emphasized in different burn populations.